Health Inspections of Restaurant Establishments in the Attica Region, Greece. Non-compliance Data Within the Food Hygiene Sector - Olympia Chatzimpyrou; Elias Chaidoutis; Dimitrios Keramydas; Petros Papalexis; Nikolaos S. Thomaidis; Vassiliki C. Pitiriga; Panagiota Langi; Foteini Koutsiari; Ioannis Drikos; Maria Giannari; Georgios Chelidonis; Andreas Ch. Lazaris; et al. (Journal of Food Protection)
Background: Ensuring food safety is a fundamental priority for public health. The catering sector has become prominent as a convenient and cost-effective method of food supply worldwide. Adherence to proper food hygiene practices is crucial for preventing foodborne diseases. The inspection of food items is a key component of internal controls that enables the identification of non-compliance with food hygiene standards. The present study aims to assess Attica restaurant businesses’ compliance with international food hygiene standards (FAO/WHO Codex Alimentarius) and European legislation on unsafe food. Methods: From January to July 2023, 74 randomly selected restaurants of small, medium, and large capacity in Attica were examined through inspections in terms of compliance for food hygiene standards. The inspections were based on (a) the completion of forms and (b) the collection of water and food samples for laboratory microbiological analysis.Data were collected using a predefined form, referencing the manual of Codex Alimentarius regarding food hygiene standards (CAC/RCP 1-1969/CAC/RCP 39-1993). Additionally, the assessment included the identification of unsafe food placement in accordance with Regulation EC/178/2002 on food safety, as well as Greek national legislation (European Commission, 2002; Hellenic Republic, 2006, 2014). Results: The highest non-compliance rates are in “adequacy of facilities” (14.12%), “equipment maintenance and sanitization” (12.30%), “pest control” (12.45%), “personal hygiene” (7.58%), and “efficient separation of raw materials” (9.76%). Non-compliance rates for other food hygiene parameters (cooking practices, meal apportionment, storage, transport, reheating, etc.) were considerably lower. The inspection results showed that medium-sized restaurant businesses present the highest rate (56.41%) of total non-compliance compared to large-sized businesses (29.68%) and small-sized businesses (13.91%). Conclusions: This study demonstrates that restaurant businesses generally adhere to food hygiene and safety standards at a satisfactory level. There is a need for restaurant operators to prioritize enhancing compliance, particularly in addressing critical issues that could potentially result in outbreaks of foodborne diseases.